Dying in Isolation: An Islamic Perspective on End-of-Life Care During COVID-19. Issue 6 (8th December 2022) - Mahmoud, Sally; Moughrabi, Samira M.; Khasawneh, Wafa F.
Abstract : COVID-19 has taken 1 million lives as of March 22, 2022. The restrictions and enforced social distancing imposed because of the COVID-19 pandemic adversely affected the way people die, often alone in hospitals without their family members or loved ones by their side. Religious and cultural beliefs predominantly influence every aspect of people's lives, especially during the end of life (EOL). Islam is the fastest growing religion worldwide after Christianity and the third most practiced religion in the United States. The Islamic religion specifies how Muslim practice health and wellness, death, and EOL care. Islamic teachings provide a roadmap on EOL practices and death rituals that must be followed by the practicing individual. Scarce empirical studies exist on practices and rituals of Muslims near death and dying. Therefore, the aim of this case report is to provide a practical framework for health care practitioners to understand essential Islamic EOL practices and provide resources to guide clinical practice.